THE INFLUENCE OF AUDITOR ETHICS, AUDITOR QUALITY, INDEPENDENCE, AND AUDITOR COMPETENCE ON FRAUD PREVENTION IN PUBLIC ACCOUNTING OFFICE IN MEDAN CITY - Aremi Evanta Br Tarigan; Johanna Gracella Tambunan; Ruth Inggrid Hutauruk; Rina Br Bukit (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Fraud is any illegal act of intentionally manipulating others or making false statements. Preventive measures must be taken to prevent significant reputational loss or reputational damage to institutions and individuals. Therefore, fraud prevention can be influenced by several variables. This study aims to detect the effect of auditor ethics, audit quality, independence and auditor competence on fraud prevention. The number of samples used in this study consisted of 60 appraisers and were processed using purposive sampling method using SPSS vers 26. The conclusion of this study results in that auditor competence has an influence on fraud prevention while auditor ethics, auditor quality and independence have no influence on fraud prevention